2008
DOI: 10.1084/jem.20072413
|View full text |Cite
|
Sign up to set email alerts
|

Copy number of FCGR3B, which is associated with systemic lupus erythematosus, correlates with protein expression and immune complex uptake

Abstract: Copy number (CN) variation (CNV) has been shown to be common in regions of the genome coding for immune-related genes, and thus impacts upon polygenic autoimmunity. Low CN of FCGR3B has recently been associated with systemic lupus erythematosus (SLE). FcγRIIIb is a glycosylphosphatidylinositol-linked, low affinity receptor for IgG found predominantly on human neutrophils. We present novel data demonstrating that both in a family with FcγRIIIb-deficiency and in the normal population, FCGR3B CNV correlates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
229
6
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(261 citation statements)
references
References 39 publications
20
229
6
6
Order By: Relevance
“…It has been hypothesised that the primary effect of deletion in the FCGR3B gene is a reduced uptake of IgG complexes, leading to tissue deposition of IC. 5,6,12,15 Our results, however, suggest that this may not be the only explanation for the observed associations. Although SLE and SSc are characterised by the presence of autoantibodies, the absence of IgG deposits in SSc is one of the major differences between SLE and SSc.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…It has been hypothesised that the primary effect of deletion in the FCGR3B gene is a reduced uptake of IgG complexes, leading to tissue deposition of IC. 5,6,12,15 Our results, however, suggest that this may not be the only explanation for the observed associations. Although SLE and SSc are characterised by the presence of autoantibodies, the absence of IgG deposits in SSc is one of the major differences between SLE and SSc.…”
Section: Discussioncontrasting
confidence: 75%
“…This is the first report in SSc and is consistent with the association reported for SLE, where published ORs range from 1.47 to 1.65. [7][8][9][10][11][12][13] Although the P value is modest (0.007), this likely represents genuine association given the prior evidence supporting a role for FCGR3B deletion in SSc. Membranebound FcgR3B is involved in the adherence of neutrophils to endothelial cells at sites of infection as well as in IC uptake.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…19 Recently, it has been found that low copy number variation of FCGRIIIB confers SLE susceptibility to patients of European origin but not to Hong Kong Chinese. 20 A major allele being a risk allele in the case of BLK is not surprising, but it may mean that the allele poses more risk to Asians on the population level. Because Asians have higher disease prevalence and more severe disease manifestations than Caucasians, it is likely that Asians may have higher genetic load than Caucasians in terms of susceptibility to the disease.…”
Section: Discussionmentioning
confidence: 99%